Pemanfaatan Gerobak Surya sebagai Implementasi Energi Terbarukan oleh UMKM Kopi di Desa Sapit - Rifqah Sajidah; Bayu Kristianto (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The awareness and knowledge of the community regarding the utilization of renewable energy in the Micro, Small, and Medium Enterprises (MSME) sector are currently not at their optimal levels. This research aims to describe the implementation and implications of a community empowerment program through socialization about renewable energy and the utilization of gerobak surya by MSMEs in Sapit Village. The research methodology employed consists of FGD and interviews. The research findings indicate an increase in community knowledge and awareness of renewable energy and its implementation through the utilization of gerobak surya by MSMEs in Sapit Village. This program has implications for the reduction of operational costs for MSMEs and facilitates access to a power source when selling or promoting their products in open spaces.